PENERAPAN KONSEP HARTA DALAM ISLAM PADA KEGIATAN EKONOMI MAHASISWA S1 EKONOMI ISLAM: Studi Kasus di UIN Sjech M. Djamil Djambek Bukittinggi - Subeno, Hadi; Taufiq, Muhammad (STAI Darul Qalam Tangerang, 2024)
A person or group of people is generally free to enjoy, spend and/or use their property/wealth without anyone to prevent it as long as the funds obtained are halal. However, private property cannot be absolute, because according to the principles of Islamic law,